Penerapan Metode Enterprise Architecture Planning (Eap) Dalam Perencaan Program Sertifikasi (Studi Kasus Laboratorium Itcc Stt-Pln) - Hendra Jatnika (KILAT, 2017)
Laboratory Information Technology Certification Center (ITCC) STT PLN is a laboratory that handles multiple certification programs an international scale, there needs to keselarasaan use of information systems and information technology in accordance with the needs of this particular time and that will come, so that the necessary frame of reference for establishing an enterprise architecture. With alsan these authors conducted a study the application of methods of Enterprise Architecture Planning (EAP), which is a method of planning oriented business requirements consist of data architecture, application and technology as well as an implementation plan of the architecture has been created to support the business activities for the attainment of the establishment of the laboratory ITCC STT PLN